Untargeted lipidomics profiling for halal authentication of meatball products from mixed meat sources - Putri Widyanti Harlina; Asad Nawaz; Raheel Shahzad; Na’Ilah Nur Amalina; Fang Geng; Mohamad Rafi; Vevi Maritha; Aldila Din Pangawikan; Souvia Rahimah; Mohammad Rizwan Khan; Widya Siva Gramita; Adelia Salsabila Nurhasya (Food Chemistry: X)
Food adulteration with non-halal components, particularly in thermally processed meat products like meatballs, presents significant challenges for conventional DNA and protein-based detection methods. This study applies untargeted lipidomics using ultra-high-performance liquid chromatography–high-resolution mass spectrometry (UHPLC–HRMS) combined with multivariate analysis (principal component analysis [PCA] and partial least squares-discriminant analysis [PLS-DA]) to authenticate halal status in meatball products. Lipid profiles were obtained from beef, goat, pork, and their mixtures, and analyzed under both electrospray ionization in positive mode (ESI+) and electrospray ionization in negative mode (ESI−) modes. Glycerophospholipids emerged as dominant lipid species. PCA and PLS-DA revealed clear separations between halal and non-halal samples, with high model performance (R2 = 0.994, Q2 = 0.952), demonstrating strong predictive capability. Five key lipid ions—lysophosphatidylethanolamine (LPE)(16:0p) + H, LPE(16:1e) + H, LPE(18:1p) + H, PC(10:0p/23:0) + H, and phosphatidylcholine (PC)(8:0/24:1) + H—were identified as markers for single-source differentiation, while twelve lipids were significant for mixed-meat products. These findings confirm the efficacy and specificity of untargeted lipidomics as a robust method for halal authentication in processed meat products.